The president's call : executive leadership from FDR to George Bush - Michaels, Judith E., 1948- (University of Pittsburgh Press, 1997)
Judith Michaels provides an in-depth examination of the Senate-confirmed presidential appointees of the Gorge H. W. Bush administration, and analyzes what these choices reveal about him, his administration, and the institution of political appointments itself. She compares this research to other administrations in the modern era. Particularly fascinating is how Bush's appointees compare with those of Ronald Reagan.
Keywords: USA -- Präsident; United States -- Officials and employees -- Selection and appointment -- History -- 20th century.; Government executives -- Selection and appointment -- United States -- History -- 20th century.; Presidents -- United States -- History -- 20th century.; United States -- Politics and government -- 1933-1945.; United States -- Politics and government -- 1945-1989.; United States -- Politics and government -- 1989-1993.; Hauts fonctionnaires -- Sélection et nomination -- États-Unis -- Histoire -- 20e siècle.; Présidents -- États-Unis -- Histoire -- 20e siècle.; États-Unis -- Politique et gouvernement -- 1933-1945.; États-Unis -- Politique et gouvernement -- 1945-1989.; États-Unis -- Politique et gouvernement -- 1989-1993.; POLITICAL SCIENCE -- Public Affairs & Administration.; Government executives -- Selection and appointment; Politics and government; Presidents; United States; Minister; Auswahl; Geschichte 1933-1993.; 1900-1999; Government executives -- Selection and appointment -- United States -- History -- 20th century; Presidents -- United States -- History -- 20th century; United States -- Officials and employees -- Selection and appointment -- History -- 20th century; United States -- Politics and government -- 1933-1945; United States -- Politics and government -- 1945-1989; United States -- Politics and government -- 1989-1993; History